2017
DOI: 10.1007/s10661-017-6338-z
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of hair to cadmium, copper and lead in five species of terrestrial mammals and implications in biomonitoring

Abstract: The capacity of mammal hair to absorb toxic metals and its utility in biomonitoring has been broadly studied. Though these metal-binding properties has generally been attributed to the sulphur contained in cysteine, an amino acid that forms part of keratin, there are not many experimental studies that analyze the role of sulphur in the external deposition of potentially toxic metallic elements in order to better understand the potential of hair in biomonitoring and generate better tools for differentiating bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Besides soft tissues some toxic elements, for instance, lead, are predominantly measured in bones [18]. On the other hand, metal concentrations in feathers are highly variable and depend on bird species and age, and for that reason some researcher state that feather samples have only low priority for ecotoxicological studies [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Besides soft tissues some toxic elements, for instance, lead, are predominantly measured in bones [18]. On the other hand, metal concentrations in feathers are highly variable and depend on bird species and age, and for that reason some researcher state that feather samples have only low priority for ecotoxicological studies [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…It has also been suggested that the metals’ absorption ability could vary in relation to several aspects, such as different hair morphology in different mammalian species. Hair is an epidermal appendage composed of three layers: the innermost layer called the medulla, composed of columns of keratinized cells; the middle layer called the cortex, in which pigment granules are contained; and the most external layer called the cuticle, composed of plates of cells characteristic for each species [ 21 , 22 ]. The differences between the three layers confer different affinities for compounds; for example, the cuticle contains sulphur, which attributes to hair the ability to absorb metals [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The differences between the three layers confer different affinities for compounds; for example, the cuticle contains sulphur, which attributes to hair the ability to absorb metals [ 23 ]. Meanwhile, the medulla and the cortex contain little or no sulphur, but both layers are embedded in pigment granules that confer the ability to selectively bind metal elements [ 21 , 22 ]. Due to these peculiar features, fur is a more reliable method for monitoring the trace and toxic elements’ status in the body than blood or urine, which are often affected by the temporary influences of some factors and are not matrices of accumulation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, hair i) can be easily collected, stored and transported, ii) can be sampled in a non-invasive manner, allowing the monitoring of threatened and/or endangered species, iii) can incorporate and retain chemicals through the hair follicle, iv) allows the elimination of toxic elements from the body when it grows, and v) can be a good indicator of the amount of Hg in the body, showing high correlation between the metal concentrations in hair and in other organs (Crowe et al 2017;Rendón-Lugo et al 2017;de Castro and de Oliveira Lima 2018;Yamanashi 2018;Eyrikh et al 2020).…”
Section: Introductionmentioning
confidence: 99%